The Meaning of Jesus’ Words "tu͂ theu͂ µu" in Revelation 3,2.12 - Kuryliak, Bohdan (Biblische Zeitschrift, 2026)
Although the Apocalypse plays a significant role in scholarly studies of New Testament Christology, scholars have largely overlooked Jesus’ words, "τοῦ θεοῦ µου" (Rev 3,2.12), which appear five times in the Apocalypse - out of a total of eight occurrences in the New Testament. This study argues that the phrase encapsulates a Christological paradox. On one hand, it points to Jesus’ unique relationship with the Father, suggesting divine equality through the thematic interplay of "God" and "Father". On the other hand, the surrounding soteriological context indicates functional subordination, as Jesus identifies with humanity in his mediatorial role. Rather than resolving this tension by favoring one interpretive path, the article proposes a paradoxical integration: Jesus is both fully divine and the representative of redeemed humanity. This dual role coheres with Revelation’s high Christology, where the Father and the Son act in unity for human salvation and are together the recipients of worship.